NON-LINEAR POST-BUCKLING LARGE DISPLACEMENT ANALYSIS FOR PLANE STEEL NON-PRISMATIC MEMBERS FRAMES WITH FLEXIBLE CONNECTIONS - AL-KHAFAJI, HAYDER NAMEER ALWASH; AL-SARRAF, SABEEH; ALWASH, NAMEER (Journal of Duhok University, 2017)
Although the joints constitute a small proportion of the total weight of the structure, but they have a comparatively large work ratio, thus the accounted is represent a large percentage of the total cost of framing. In addition, the contact region deformation is sometimes responsible for a significant proportion of the total deviation of the structure and often has a large impact on the distribution of internal distribution of the forces. All real structures show nonlinear behavior when loads and deformations become large enough and the tapered members are also used in several locations in the structural applications such as aerospace structures, bridges, as well, in many mechanical components. It is used to try to meet the architectural requirements for the shape of buildings and to achieve a suitable division of strength and weight. So, the nonlinear post-buckling behavior of plane steel frame under loads was a major research topic. A general formulation of Eulerian is used to analyze the plane frames and it is clear that this method of analysis are be good to use within theory of  beam-column. This study is shown that a polynomial modeling of the non-linear moment-rotation curve of steel connection gives excellent results with the exact non-linear moment-rotation curve with a difference not more than (1%) and the effect of the flexible connections must be considered in the analysis because it has significant effect on the behavior of the steel structures and the new modified tangent stiffness matrix which takes into account the two types of non-linearities at the same time (i.e. geometry and connection) and non-prismatic members efficient in giving accurate results of analysis of different types frames with difference not more than (0.5%) compere with the other finite element methods for analysis